Pengaruh Kecerdasan Emosional dan PerilakuBelajar Terhadap Tingkat Pemahaman AkuntansiMahasiswa (Studi Empiris Mahasiswa Akuntansi Perguruan Tinggi di KotaPadang) - Atika Mutia (Wahana Riset Akuntansi, 2015)
The purpose of this study is to get empirical evidence about the extent of the influence of emotional intelligence , learning behavior of the level understanding of accounting students . This study classified causative research . The study population was a college accounting students in Padang . The sample is determined based on purposive sampling method by 4 colleges in Padang, with respondents as many as 120 accounting students . Methods of data collection using the questionnaire . Types and sources of data are the primary data . Analysis of data using multiple regression with F test and t test.The results of this study indicated ( 1 ) emotional intelligence positive significant effect on the level understanding of accounting students ( 2 ) learning behavior positive significant effect on the level understanding of accountingstudents. Keywords : emotional intelligence , learning behavior , the level understanding of accounting students